Mitigating the effects of high biomass algal blooms on the drinking water intakes of the city of Buenos Aires, Argentina - Silva, C.; Marti, Clelia; Imberger, J. (2014)
© 2014 International Association for Hydro-Environment Engineering and Research. Three-dimensional hydrodynamic and ecological modelling was used to explore strategies to mitigate the impacts of high biomass algal blooms (Aulacoseira sp.) on the drinking water intakes of the city of Buenos Aires, in the Río de la Plata. An automated real-time and a four-day forecast warning system was implemented in 2010 in order to predict the occurrence of such blooms near the intakes. Since the adoption of the technology, blooms of Aulacoseira sp. were neither predicted nor observed, demonstrating that the system did not create a false positive. Further, a historical high biomass bloom event was successfully predicted and then used to test two engineering solutions, designed to mitigate the impact of strong blooms. It was found that extending the raw drinking water intakes offshore beyond the high algae concentration provided a 50% reduction in Aulacoseira sp. concentrations. Alternatively, placing groynes around the intake sites induced a dilution of the phytoplankton patch and reduced the concentrations by 40%.